Fostering Learning Base Digital Mind Maps To Improve Student’s Problem-Solving Skills in Senior High Schools - Ningsih Fahruddin; Yenita Zuriani; Bagus Endri Yanto (AL-ISHLAH: Jurnal Pendidikan, 2025)
Problem-solving skills are essential for fostering creativity and enhancing students' decision-making abilities. One promising strategy to develop these skills is through active learning using digital mind maps, which help students visually structure and connect information. This study employed a quasi-experimental, non-equivalent control group design to assess the effectiveness of digital mind maps in enhancing problem-solving skills. A total of 100 students were selected through cluster sampling. The experimental group engaged in active learning using digital mind maps, while the control group followed a traditional learning approach. Data were collected using standardized test instruments, with validity evaluated through the Aiken index and reliability measured using Cronbach’s alpha. Quantitative descriptive analysis was used to interpret the results. The findings showed a statistically significant improvement in problem-solving skills among students in the experimental group compared to the control group (Sig = 0.00 α), indicating the effectiveness of digital mind maps in facilitating learning. The use of digital mind maps within an active learning framework significantly enhances students' ability to solve problems. This method not only supports the development of critical thinking and decision-making skills but also promotes a shift in how students process and engage with information in science education. Digital mind maps are an effective active learning tool for improving students' problem-solving abilities and have meaningful implications for educational practices.